Evaluasi Kualitas Perangkat Lunak Sistem Absensi Pegawai Berbasis Framework Laravel Menggunakan ISO 29119 (Studi Kasus :Absensi-Pegawai-qr-code) - Leonard Attalah; Muhamad Ikbal Kholik Saepullah; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
This study aims to assess the quality of Employee Attendance System software by referring to the ISO/IEC 29119 software testing standard. This application was created using Laravel and Vue.js to manage employee attendance, leave, and permissions. One of the main problems that often arise in the attendance system is failure in input data validation, potential security vulnerabilities, and logical errors in the check-in/check-out process that can seriously impact the reliability of employee data. In this study, an organized testing methodology is used that includes test planning, test scenario development, and test execution in accordance with ISO/IEC 29119-2 clauses with a risk-based method. The testing methods applied are Black Box Testing using Equivalence Partitioning techniques to verify the functionality between input and output, and White Box Testing with Cyclomatic Complexity analysis to assess the efficiency of the code's logical structure. The testing process was carried out by compiling 25 comprehensive test scenarios covering positive and negative conditions. The test results successfully found 10 software bugs with varying levels of severity, including critical issues such as weak validation of GPS location input and Cross-Site Scripting vulnerabilities. In conclusion, the implementation of the ISO/IEC 29119 standard has proven to be able to systematically organize the quality assurance process, detect security vulnerabilities early on, and provide important technical improvement recommendations before the system is operational to ensure system reliability.